Other Practices: Gendering Histories of Architecture - Hultzsch, Anne (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
“To write women back into history”, is an often-used phrase in recent feminist discourse. More and more scholars work to increase the visibility of those women who took charge of design projects in the recent and not so recent past. While crucial, such efforts are, in the paradox way of how privilege works, to an extent counterproductive: presenting these women (and other, historically marginalised figures) as exceptions from the rule – as eccentric trailblazers  - implies the majority of their female (or Black, indigenous, queer, other ...) contemporaries had no influence within (white, male) architectural practices. This position paper argues that we also need to look for other practices that enabled women (and others) in greater numbers to gain agency. Writing is one such practice: the recording of experience, critiques, and instructions to appropriate the designed, ascribing meaning to architectures and landscapes. Locating architectural agency in a practice that, while presuming some privilege, was much more open to marginalised groups than that of the architect, enables us to look at the past more inclusively: to write gendered histories that open up spaces for those that were there, in fact.
Keywords: Women Architects; Female Writing; Gender; Alternatives Professionals; Feminist practices; Historiography